REDUCING RESOURCE DEPENDENCE ON GOVERNMENT FUNDING OF PUBLIC UNIVERSITIES (Journal of Association of Educational Management and Policy Practitioners, 2024)
This paper investigated how public universities can leverage their dependence on government funding. Organization of the paper began with an introduction that set forth the topic parameter and its rationale. This is followed by conceptual understanding of dependence and the issues therein. Government funding of public universities is fraught with so many challenges, such as fluctuations, cuts, regulations, and laws, which limit the conducts of public universities. In order to reduce public universities dependence on government funding, strategies by which they could gain greater resources were highlighted to include: university administrators to adapt management model to the needs of the external environment from which the university could draw various resources, influence the environment to improve their functioning conditions, build strong board to diversify revenues, strategic planning, working in unity to increase efficiency and effectiveness, etc. The work also pointed out some of the financial connectivity pathways like public university engagement on Internally Generated Revenue (IGR) for profit making venture, setting up endowment support for programmes, collaboration with public/private partnership, attracting wealthy individuals to take up finance of capital projects to immortalize their names, establishment of non-proprietor funding sources and so on. Suggestions included that public universities should be made to charge tuition fees within government parameters and redesign policies that would enable public university system to be self-sustaining, amongst others. The paper concluded that implementing the suggestions can help to maintain financial stability, which will reduce public university dependence on government funding.